Struggling for Multiculturalism: The Revival of Chinese Festivals in Three Cities of Java during the Post-Reformation Era and Its Challenges - Evi Lina Sutrisno (Humaniora, 2023)
In the Reformation era, the Chinese-Indonesians enjoy more freedom in expressing their ethnic identity in the public sphere, which was once oppressed under Soeharto’s New Order (1967-1998). The return of the Chinese festivals appears to indicate the end of discrimination and the celebration of multiculturalism, which recognizes the acculturation between the Chinese and local cultures. However, several festivals received backlash and resentment from local Islamic groups. Based on fieldwork and observation on the Chinese New Year folk festivals 2019-2020 in Semarang, Solo, and Yogyakarta, this article describes the socio-political dimensions behind the revival of Chinese New Year folk festivals. The findings show that while Chinese cultural icons become obvious, these folk festivals accommodate the acculturation between the Chinese and local ethnic and/or religious cultures, which made them closer to the expression of hybrid and multicultural identities. However, the Islamic groups still felt the exposure of Chinese culture was beyond limit and the hybridity is disturbing the Islamic faith. They protested to limit or cancel these festivals. In mitigating the protests and conflicts, the local governments tend to take pragmatic problem solutions, rather than educating the public regarding multiculturalism and tolerance.